Quadrivalent inactivated influenza vaccine (VaxigripTetra™) - Viviane Gresset-Bourgeois; Phillip S. Leventhal; Stéphanie Pepin; Rosalind Hollingsworth; Marie-Pierre; Iris De Bruijn; Sandrine I. Samson (Taylor & Francis Group, 2018)
Introduction: VaxigripTetra™ (IIV4; Sanofi Pasteur) is a quadrivalent split-virion influenza vaccine approved in Europe in 2016 for individuals ≥ 3 years of age. IIV4 builds on the well-established record of the trivalent split-virion influenza vaccine (Vaxigrip®). Areas covered: This literature review summarizes the rationale for developing quadrivalent influenza vaccines and discusses the phase III clinical trial results supporting the immunogenicity, safety, and tolerability of IIV4. Expert commentary: IIV4 is immunogenic and well tolerated. Adding a second B strain to the trivalent split-virion influenza vaccine provides a superior immune response for the additional strain but does not reduce the immune response for the three other strains or negatively affect the safety profile. By offering broader protection against co-circulating influenza B lineages, IIV4 has the potential to further reduce influenza-related morbidity and mortality beyond that achieved with trivalent vaccines.